ANALISIS PENGARUH CUSTOMER EXPERIENCE TERHADAP MINAT BELI KONSUMEN DI BENGKEL BURGER & BRE X KAREN'S DINER - Stephanie Ivana Lasmana; Rendy Sarudin (LPPM Institut Pendidikan Nusantara Global, 2023)
This research was made with the aim of analyzing the relationship between Customer Experience and Consumer Purchase Interest and how much influence Customer Experience has on Consumer Purchase Interest. Based on the results of tests conducted by researchers in this study, it proves that there is a significant influence from customer experience on consumer buying interest at Bengkel Burger & Brew X Karen's Diner. This is evidenced by the results of the t test with a tcount of 17.879 > ttable 1.98447 with a significance of 0.000. In addition to the t test, the results of the Multicollinearity Test show that the tolerance value is 1.000 > 0.10 and the VIF value is 1.000 <10.00, this means that multicollinearity does not occur. Based on the results of the Heteroscedasticity Test with a significance value of 0.154, > 0.05, it can be concluded that the data used by the researchers in this study had no problems with heteroscedasticity. And based on the results of the Coefficient of Determination Test (R2), it can be seen that the value of R2 is 0.765 which means that the effect of variable X on variable Y is 76.5% with the remaining 23.5% influenced by other variables not examined in this study.